PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PT. RAMAJAYA PRAMUKTI KECAMATAN TAPUNG KABUPATEN KAMPAR PROVINSI RIAU - Safitri, Dini; Indarti, Sri; fitri, kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to test and prove empirically: direct or indirect influence of leadership and organizational commitment towards job satisfaction and employee performance. The population of the research was the employee remains employed at PT. Ramajaya Pramukti Tapung Subdistrict. The sample in this study were 129 employees from the entire population of permanent employees totalling 191 employees. Research samples taken by random sampling. Data collection techniques are used, namely by giving questionnaires and observation. Data analysis was done with the analysis line. The results of this research indicate that: Influential leadership positively and significantly to job satisfaction. The organization's commitment to a positive and significant effect against the job satisfaction. The leadership to a positive and significant effect on performance through job satisfaction. The organization's commitment to a positive and significant effect on performance through job satisfaction. Job satisfaction the positive and significant effect on performance. Good leadership and high organizational commitment will affect job satisfaction and improved employee performance PT. Ramajaya Pramukti Subdistrict Tapung Counties Kampar the Province of Riau.Keywords : leadership, organizational commitment, job satisfaction and employee performance